IOT based modeling of closed transition transfer switch in IEC 61850 - Sung Lim, Hyun; Ho Ryu, In; Ho Bang, Jun (International Journal of Engineering and Technology, 2018)
Background/Objectives: The power demand of utility electrical power has stimulated the use of distributed energy for peak shaving. Distributed energy resources need to be monitored and controlled like Internet of Things.Methods/Statistical analysis: Distributed Energy Resources (DERs) are small scale electric energy system like Micro Turbine, Photovoltaic, Wind power, Small Generator and widely spread in Korea. For utilizing electrical device with Internet of Things, we need integrated system and adapt International Electrical Code like IEC 61850.Findings: To connect DERs with uninterrupted grid system, it required Closed Transition Transfer Switch (CTTS). Existing International Electrical Code presented some distributed energy resource by IEC 61850-7-420. However, the switch like CTTS is not presented. So, we described modeling of CTTS in IEC 61850 and verified monitoring data with TCP/IP.Improvements/Applications: The proposed modeling of CTTS not only combines the DERs with grid system but also conjugates smart grid system with IOT Technology.Â